Accuracy of a new online method for measuring machining parameters in milling. (November 2018) - Leal-Muñoz, E.; Diez, E.; Perez, H.; Vizan, A.
Highlights: Novel method for axial and radial depth estimation from a single measured cutting force component. Influence of the cutting parameters on system dynamics to improve the estimation of axial depth is studied. A sensitivity and uncertainty analysis was carried out to ensure robustness of the methodology. Results show a high accuracy and low uncertainty for different tools and cutting conditions. Abstract: The development of new methodologies to monitor, control and optimize manufacturing systems is on the increase. In this sense, the aim of this paper is to analyze the accuracy of an online method for measuring machining parameters from cutting force signals in milling processes. The method is based on time measurement which, in principle, provides sufficient precision to detect minor variations in cutting parameters. In order to assess the accuracy of the method, the sensitivity and uncertainty of the variables involved have been determined, classifying them according to their influence on the results. The dynamic response of the tool may affect the accuracy of the measurement. For this reason, a function that relates the response time to the input variables in the process is determined. The force signal is obtained with a dynamometric platform using piezoelectric sensors, which provides robustness to the proposed measurement method. The results of the measurement of depths of cut show a high degree of precision with uncertainties below 4%.